Serine proteases as luminal mediators of intestinal barrier dysfunction and symptom severity in IBS. Issue 1 (28th March 2019) - Edogawa, Shoko; Edwinson, Adam L; Peters, Stephanie A; Chikkamenahalli, Lakshmikanth L; Sundt, Wendy; Graves, Sara; Gurunathan, Sakteesh V; Breen-Lyles, Margaret; Johnson, Stephen; Dyer, Roy; Graham, Rondell; Chen, Jun; et al.
Abstract : Objective: The intestinal lumen contains several proteases. Our aim was to determine the role of faecal proteases in mediating barrier dysfunction and symptoms in IBS. Design: 39 patients with IBS and 25 healthy volunteers completed questionnaires, assessments of in vivo permeability, ex vivo colonic barrier function in Ussing chambers, tight junction (TJ) proteins, ultrastructural morphology and 16 s sequencing of faecal microbiota rRNA. A casein-based assay was used to measure proteolytic activity (PA) in faecal supernatants (FSNs). Colonic barrier function was determined in mice (ex-germ free) humanised with microbial communities associated with different human PA states. Results: Patients with IBS had higher faecal PA than healthy volunteers. 8/20 postinfection IBS (PI-IBS) and 3/19 constipation- predominant IBS had high PA (>95th percentile). High-PA patients had more and looser bowel movements, greater symptom severity and higher in vivo and ex vivo colonic permeability. High-PA FSNs increased paracellular permeability, decreased occludin and increased phosphorylated myosin light chain (pMLC) expression. Serine but not cysteine protease inhibitor significantly blocked high-PA FSN effects on barrier. The effects on barrier were diminished by pharmacological or siRNA inhibition of protease activated receptor-2 (PAR-2). Patients with high-PA IBS had lower occludin expression, wider TJs on biopsies and reduced microbial diversity than patients with low PA. Mice humanised with high-PA IBS microbiota had greater in vivo permeability than those with low-PA microbiota. Conclusion: A subset of patients with IBS, especially in PI-IBS, has substantially high faecal PA, greater symptoms, impaired barrier and reduced microbial diversity. Commensal microbiota affects luminal PA that can influence host barrier function.